Alveolar Macrophages Treated With Bacillus subtilis Spore Protect Mice Infected With Respiratory Syncytial Virus A2 - Hong, Ji Eun; Kye, Yoon-Chul; Park, Sung-Moo; Cheon, In Su; Chu, Hyuk; Park, Byung-Chul; Park, Yeong-Min; Chang, Jun; Cho, Jae-Ho; Song, Man Ki; Han, Seung Hyun; Yun, Cheol-Heui (Frontiers in Microbiology, 2019)
Respiratory syncytial virus (RSV) is a major pathogen that infects lower respiratory tract and causes a common respiratory disease. Despite serious pathological consequences with this virus, effective treatments for controlling RSV infection remain unsolved, along with poor innate immune responses induced at the initial stage of RSV infection. Such a poor innate defense mechanism against RSV leads us to study a role of alveolar macrophage (AM) that is one of the primary innate immune cell types in the respiratory tract and may contribute to protective responses against RSV infection. As an effective strategy for enhancing anti-viral function of AM, this study suggests the intranasal administration of Bacillus subtilis spore which induces expansion of AM in the lung with activation and enhanced production of inflammatory cytokines along with several genes associated with M1 macrophage differentiation. Such effect by spore on AM was largely dependent on TLR-MyD88 signaling and, most importantly, resulted in a profound reduction of viral titers and pathological lung injury upon RSV infection. Taken together, our results suggest a protective role of AM in RSV infection and its functional modulation by Bacillus subtilis spore, which may be a useful and potential therapeutic approach against RSV.